Teknik Budidaya Rumput Laut (Kappaphycus alvarezii) dengan Metode Rakit Apung di Desa Tanjung, Kecamatan Saronggi, Kabupaten Sumenep, Jawa Timur [Technique Culture of Sea Weed (Kappaphycus alvarezii) with Flouting Raft Method in Tanjung Village, Saronggi Sub District, Sumenep Regency, East Java] - Annur Ahadi Abdullah (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
Abstract Sea weed is a great culture commodity with high economical value. The purpose of this Field Job Practice were to get knowledge and skill ,the constraint, and also the opportunity to develop it. This Field Job st thPractice performed in Tanjung Village at July 31 until September 10  2006 used description method. Sea weed culture techique use flouting raft with raft size 7 x 10 m and string distance 14 cm  with culture 30 days period. The constraint  are pest attack like Baronang (Siganus sp.), ice ice, white spot disease and also weather fluctuation.This culture has opportunity to develop because  it has fast cash back about 2,176 periode.